Industrial symbiosis in Australia: The social relations of making contact in a matchmaking marketplace for SMEs. (10th October 2020) - King, Sarah; Lusher, Dean; Hopkins, John; Simpson, Gregory W.
Abstract: This research investigates a new Australian industrial symbiosis network case (known as ASPIRE) and the social relations of inter-organisation contact, as a precursor to a waste transfer in an industrial symbiosis matchmaking market. The application of exponential random graph models allow testing at the node, dyad and network level to identify companies that are more likely to engage with the goals of the project. The research findings indicate that endogenous network features are largely silent whereas attribute-based, exogenous features play a significant role in companies making contact for industrial symbiosis opportunities. Companies identifying as recyclers have a central role in sending and receiving contact ties. Recyclers are a key consideration for facilitators maintaining a two-sided marketplace and are likely to operate as 'pioneer species' in the establishment of an industrial symbiosis network for SMEs. We also found that facilitator contact with companies, pre-existing personal relationships, and companies interested in future use of recycled materials, are more likely to send contact ties. Geographic proximity was not found to be significant for companies making contact within this network. The implications for program governance are that facilitators may identify companies more likely to engage with the program, which could lead to improved network effectiveness. Facilitators play a crucial role in the network and it is important that they monitor the recruitment of companies to balance the two-sided market and its ongoing success. The ASPIRE case provides an alternative model to heavy industry, self-organised industrial symbiosis such as Kwinana and is more applicable to urban regions and SMEs. Highlights: ASPIRE supports industrial symbiosis for Australian SMEs and urban locations. Application of exponential random graph models to an industrial symbiosis network. Recyclers act as 'pioneer species' for ASPIRE in sending and receiving contact ties. Recyclers balance the two-sided marketplace. Council facilitators are vital link between digital/social elements of marketplaces.